Penerapan Konseling Individu dengan Teknik Modeling dalam Mengatasi Kecanduan Pornografi pada Remaja - M. Syafiqri Meidiansyah (Journal of Society Counseling, 2025)
This study is entitled "Implementation of Individual Counseling with Modeling Techniques in Overcoming Pornography Addiction in Adolescents (Case Study of Client A in Mulia Agung Village)". Pornography addiction is a behavior where a person cannot control their desire to continuously consume pornographic content in the form of images, videos, or other media that stimulate sexuality. This study aims to provide understanding, knowledge, and education to clients about the negative impacts of pornography addiction, recognizing addiction triggers, and effective ways to overcome these urges. This study is a type of qualitative research with a case study method. The data collection techniques used are observation, interview, and documentation methods. While the data analysis techniques used are by means of pattern matching, data explanation, and time series analysis. The results of this study indicate that before the implementation of individual counseling with modeling techniques, Client-A experienced various symptoms of pornography addiction, such as difficulty controlling the desire to access pornographic content, feelings of restlessness, anxiety, and difficulty concentrating and interacting socially. Client A also often experiences emotional instability and feels decreased self-confidence. However, after individual counseling with modeling techniques, Client A showed significant changes, where Client A managed to develop better self-control, understand the negative impacts of his habits, and began to replace harmful behaviors with more positive and beneficial activities. The support and encouragement provided during the counseling process helped Client A build a healthier mindset, enabling them to continue maintaining these positive changes and develop further in the future.